O relacionamento entre filhos adolescentes e seus pais e mães em um contexto de violência doméstica e familiar contra a mulher - Justino, Yara Alves Costa (2017)
This study sought to investigate, based on the perspective of children, how the relationship between adolescent children and their parents is established in families who experience / have experienced domestic and family violence against women. For that, we interviewed 11 adolescents between 12 and 16 years of age, of both sexes, members of families in which there was identification of domestic and family violence against the woman, perpetrated by the father against the mother of the adolescent. There was institutional mediation of the Coordination of Assistance to Victims of Domestic Violence and Discrimination (CAVVID), located in Vitória-ES, and the Secretariat of Public Policies for Women (SEPPOM), located in Serra-ES, to identify the participants. The interviews took place on the basis of a semistructured script, which was inspired by the Family Interaction Quality Scale (EQIF). Questions addressed the evaluation of the children on the family environment, specifically adolescent's relationship with the mother and the father, the way in which teens evaluated the relationship between mother and father and how that relationship affected parenting. Interviews were recorded and fully transcribed and then categorized and analyzed based on the content analysis method. Discussion of the results took place in the light of Bioecological Theory of Human Development and the literature on the subject. The data indicated that adolescents perceived conflict situations between the father and the mother in the family microsystem, which affect them. Specifically regarding the relationship with the father, the adolescents highlighted negative feelings, complaining about the father's lack of availability to be with his children, his aggressive behavior towards the mother and other family members, and the consumption of alcoholic drinks by the father. With regard to the positive aspects, the adolescents reported the material support, moments of care and expression of affection. On the other hand, almost all adolescents described the relationship with the mother as positive. Moments of care, monitoring, expression of affection, joint activities with the mother and feeling of support in the relationship were mentioned. The negative aspects described referred to the occurrence of disagreements for reasons related to limits imposed by the mother, divergent opinions, as well as situations that involved the relationship with the father. Considering that, for the most part, the adolescents evaluated the relationship with the mother positively; the analysis showed that the proximal processes with the mother can contribute to attenuate the negative effects of the coexistence in the family, described by the adolescents. The data obtained reinforce the importance of expanding studies on the impact of domestic violence on parenting from the point of view of all family members, as well as expanding the support network also to children who experience conflicts involving parental figures, helping families to stop the cycle of violence.